Basil Leaf Essensial Oil (Ocimum × africanum Lour.) and It’s Effectiveness as Anti-Mosquito Lotion against Aedes aegypti (Linnaeus, 1762) - Yanti, Ni Luh Made Yuli Indra; Arpiwi, Ni Luh; Yulihastuti, Dwi Ariani (Metamorfosa: Journal of Biological Sciences, 2020)
Aedes aegypti  L. mosquito is the vector of dengue fever disease. The effort to control the vector is by applying anti-mosquito lotion to the skin. Basil essential oil was formulated into anttimosquito lotions which is practice and easy to be carried anywhere.  The use of atimosquito lotion with natural active compound of basil essential oil is one of safe solutions to repelt mosquitos. This study aimed to calculate yield of essential oil from basil leaves, to identify the active compounds, to measure protection ability of the antimosquito lotions, to to anlyse physical properties of the lotions and to analyse perception of panelists toward the lotions. The essential oil was extracted using steam distillation. The active compounds were analysed using GS-MS. Protection ability of the lotion toard Ae. aegypti L. was tested under laboratory condition using hand in cage method. Physical properties of the lotion were measured for organoleptic, pH, viscosity and homogeneity. Results showed that the yield of essential oil from basil leaves was 0,26% ± 0,05 w/w. GCMS test results showed there were 25 active compounds of the oil. The highest protection ability against A aegypti L. was lotion with 5% basil essential oil. Organoleptic test results show a thick texture, yellowish white color, aroma of olive oil and basil and a soft impression on the skin. Results of pH, viscosity and homogeneity tests show that anti-mosquito lotions containing essential oil from basil leaves met the requirements in the Indonesian National Standard. The hedonic test shows that panelists like lotion with 5% basil essential oil. The effect of lotion gives softness, comfort and the absence of sensitivity symptoms after being applied to the skin. Keywords:  Aedes aegypti  mosquito, dengue fever, basil essential oil, lotion.